Changing the corporate elite? Not so easy. Female directors' appointments onto corporate boards - Aleksandra Gregoriéc; Lars Oxelheim; Trond Randøy; Steen Thomsen (Research Institute of Industrial Economics (IFN), 2013)
Scholars have previously investigated country and organizational-level factors associated with the incidence of female directors on boards. These studies, however, cannot explain why, in countries with strong gender equality and pressure for female directorships, firms are still hesitant to promote new women to their boards. To address this issue we - in this study - introduce the cognitive and affective processes related to directors' identification with the traditional corporate elite as an explanation for the slow organizational response to pressure for gender diversity on boards. We bridge the social identity and critical mass theory to further show how these responses may vary with the current composition of the board. Viewing the board as a locus for the maintenance of the positive distinctiveness of the established corporate elite, we conjecture that new female appointments will not only depend on the current share of women on board but also on the current (minority) share of board positions held by male directors who are not prototypical of the established elite. We also uncover how this relationship is moderated by the share of institutional investors' ownership. We test and support these propositions on a sample of 387 publicly traded Nordic corporations during 2001-2008.
Keywords: D22; F23; F66; G34; M16; 330; social identity; board of director; gender diversity